Exploratory study of the hoaxes spread via WhatsApp in Spain to prevent and/or cure COVID-19 - Carolina Moreno-Castro; Empar Vengut-Climent; Lorena Cano-Orón; Isabel Mendoza-Poudereux (Elsevier, 2021)
Objective: To review the hoaxes' characteristics spread through WhatsApp in Spain during COVID-19 lockdown and identify what kind of substances were promoted for consumption or application. Method: A phone number was activated to receive hoaxes via WhatsApp. A total of 2353 messages were collected, and among those 584 different hoaxes were identified and validated, between March 18 and April 18, 2020. From these 584 hoaxes, a sub-sample of 126 was selected, exclusively related to the object of study, and a content analysis table with fourteen registration fields was applied. Besides, the averages and medians of the quantitative fields were extracted. Results: Most of the messages received were texts (39%) and videos (30%). In the majority, the acting subject was presented as medical personnel (36.5%) or as an anonymous person (30.9%). The videos lasted between 2' 40" and 18' 18", while the audios ranged between 1' 35" and 7' 48". Regarding the gender of the informant, there was a significant difference, with 45.2% being male, and 13.5%, female and 41.3% non-identifiable. Conclusions: One out of five false health claims received was about prevention or cure of the coronavirus, based on the principle of medical authority, and basically promoting the use and consumption of substances of natural origin. Resumen: Objetivo: Examinar las características de los bulos difundidos por WhatsApp en España durante el confinamiento por la pandemia de COVID-19 e identificar qué tipo de sustancias se promovieron para su ingesta o uso. Método: Se habilitó un número de teléfono para recibir bulos por WhatsApp. Se recibieron 2353 mensajes, de los que se identificaron y validaron 584 bulos distintos, entre el 18 de marzo y el 18 de abril de 2020. De los 584 bulos, se seleccionó una submuestra de 126 relacionados con el objeto de estudio y se aplicó una ficha de análisis de contenido con 14 campos de registro. Además, se extrajeron las medias y medianas de los campos cuantitativos. Resultados: La mayor parte de los mensajes fueron cadenas de texto (39%) y vídeos (30%). En la mayoría, el sujeto se presentaba como personal médico (36,5%) o como persona anónima (30,9%). Los vídeos tuvieron una duración de entre 2' 40" y 18' 18", mientras que los audios fueron de entre 1' 35" y 7' 48". Con respecto al sexo, se apreció una gran diferencia: el 45,2% de los protagonistas fueron hombres, frente al 13,5% de mujeres; el 41,3% no era identificable. Conclusiones: Uno de cada cinco bulos recibidos fue sobre prevención o curación del coronavirus, argumentados sobre el principio de autoridad médica y básicamente promoviendo el uso y consumo de sustancias de origen natural.